Beneficial effects of L-ornithine L-aspartate for prevention of overt hepatic encephalopathy in patients with cirrhosis: a systematic review with meta-analysis - Butterworth, Roger F. (Metab Brain Dis, 2019)
The present systematic review with meta-analysis was undertaken to review the evidence base in support of a beneficial effect of L-ornithine L-aspartate (LOLA) for the prevention/prophylaxis of overt hepatic encephalopathy (OHE) in patients with cirrhosis. Using appropriate keywords and electronic and manual searches together with established inclusion/exclusion criteria, six randomized controlled trials (RCTs) for a total of 384 patients were identified five of which were of high quality and low risk of bias according to Jadad-Cochrane criteria. Treatment with LOLA resulted in significant reductions in the risk of progression to OHE in MHE patients (3 studies) with RR: 0.23 [95% CI: 0.07, 0.73], p < 0.01. LOLA was also effective for secondary OHE prophylaxis with RR: 0.389 [95% CI: 0.174–0.870] p < 0.002 as well as for primary prophylaxis for OHE following acute variceal bleeding [RR: 0.42 [95% CI: 0.16–0.98] p < 0.03 and for OHE prophylaxis post-TIPSS [RR: 0.30 [95% CI: 0.03–2.66] compared to placebo/no intervention in all cases. OHE prevention/prophylaxis was accompanied by significant reductions of blood ammonia. Both oral and intravenous formulations of LOLA appeared to be effective for the prevention of progression to OHE in patients with MHE. These findings provide the first direct evidence of potential benefit of LOLA for the prevention of OHE in cirrhosis across a range of clinical presentations.